2017
DOI: 10.1142/s0218127417300221
|View full text |Cite
|
Sign up to set email alerts
|

On Discontinuous Piecewise Linear Models for Memristor Oscillators

Abstract: In this paper, we provide for the first time rigorous mathematical results regarding the rich dynamics of piecewise linear memristor oscillators. In particular, for each nonlinear oscillator given in [Itoh & Chua, 2008], we show the existence of an infinite family of invariant manifolds and that the dynamics on such manifolds can be modeled without resorting to discontinuous models. Our approach provides topologically equivalent continuous models with one dimension less but with one extra parameter associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 19 publications
1
13
0
Order By: Relevance
“…1. The frequency ω 0 is assumed to be a given positive constant due to the periodic input, while the offset A, the amplitude B, B > 0, and the phase difference Φ 0 , Φ 0 ∈ [0, 2π), between y 0 (τ ) and the harmonic forcing term in (25) are unknown.…”
Section: Computation Of Ppss Via the Hbmmentioning
confidence: 99%
See 2 more Smart Citations
“…1. The frequency ω 0 is assumed to be a given positive constant due to the periodic input, while the offset A, the amplitude B, B > 0, and the phase difference Φ 0 , Φ 0 ∈ [0, 2π), between y 0 (τ ) and the harmonic forcing term in (25) are unknown.…”
Section: Computation Of Ppss Via the Hbmmentioning
confidence: 99%
“…The HBM consists in first substituting the approximation ( 26) into (25), then balancing the continuous and the first harmonic terms, and finally solving for A, B and Φ 0 the resulting system of equations. To proceed,…”
Section: Computation Of Ppss Via the Hbmmentioning
confidence: 99%
See 1 more Smart Citation
“…Later, it became clear that the state space of circuits containing ideal memristors can be decomposed into a continuum of invariant manifolds (foliation property of the state space), which are indexed by some constant parameter whose value depends on the initial conditions of the circuit. Specifically, in [22,23] a third-order memristor circuit is investigated in the voltage-current domain, while quite general classes of memristor circuits are analyzed in the flux-charge domain (see [24][25][26][27] and references therein). In particular, the flux-charge analysis method (FCAM), introduced in [24,25], makes it clear that the rich dynamics displayed by memristor circuits is due to the fact that the state space contains infinitely many invariant manifolds.…”
Section: Introductionmentioning
confidence: 99%
“…it can be decomposed in a continuum of invariant manifolds where the circuit dynamics is described by a reduced order system. Specifically, in [Amador et al, 2017;Ponce et al, 2017] it is shown that the dynamics of a third order memristor circuit admits a first integral in the current-voltage domain and hence it can be equivalently described by a family of second order systems indexed by an additional constant parameter. Notably, the existence of a first integral implies that the second order systems have a smoother vector field, which is a useful property when the memristor has a piecewise linear characteristic.…”
Section: Introductionmentioning
confidence: 99%